Cyclic Coupled Fixed Point Result Using Kannan Type Contractions. (2nd July 2014) - Choudhury, Binayak S.; Maity, Pranati
Abstract : Putting several existing ideas together, in this paper we define the concept of cyclic coupled Kannan type contraction. We establish a strong coupled fixed point theorem for such mappings. The theorem is supported with an illustrative example.